2001
DOI: 10.1177/1358836x0100600405
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial disease and depressed mood in older men and women

Abstract: The objective of this study was to determine whether lower extremity peripheral arterial disease (PAD) is associated with depressive symptoms and whether PAD-related disability mediates the association between PAD and depressive symptoms. The study used a cross-sectional design set in an academic medical center. A cohort of men and women aged 55 years and older with (n = 93) or without (n = 74) PAD was recruited. PAD subjects were identified from a blood flow laboratory and a general medicine practice. Non-PAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
41
1
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(48 citation statements)
references
References 32 publications
3
41
1
3
Order By: Relevance
“…Both PAD and stroke history were the strongest independent variables associated with depression and there were univariate associations with ischaemic infarcts in a subsample of patients with available neuroimaging. A link between PAD and depression in a cross-sectional clinicbased study was thought to be due to associated disability [45]. The Atherosclerosis Risk in Communities Study reported a modest association between baseline depressive symptoms and incident PAD [46].…”
Section: Discussionmentioning
confidence: 99%
“…Both PAD and stroke history were the strongest independent variables associated with depression and there were univariate associations with ischaemic infarcts in a subsample of patients with available neuroimaging. A link between PAD and depression in a cross-sectional clinicbased study was thought to be due to associated disability [45]. The Atherosclerosis Risk in Communities Study reported a modest association between baseline depressive symptoms and incident PAD [46].…”
Section: Discussionmentioning
confidence: 99%
“…[5][6][7] For patients with acute coronary syndromes, depression is a risk factor for recurrent cardiovascular events and mortality. [8][9][10] After coronary artery bypass surgery, it is associated with increased risk for recurrent cardiovascular events, 4,11 rehospitalization for cardiac events, 12 repeat coronary revascularization, 4 and death.…”
Section: Introductionmentioning
confidence: 99%
“…Extra-coronary atherosclerosis (a combined measurement) was found to be associated with increased odds of having depressive disorders, although the relationship between ABI and depressive disorders alone was not significant. The lack of positive relationship in the study by Arseven et al [9] could be due to the small sample size. On the other hand, the lack of association between ABI and depressive disorders in the study by Tiemier et al [10] could be due to differences in the severity of peripheral atherosclerosis when compared to those in our study.…”
Section: Discussionmentioning
confidence: 81%
“…Previous studies on the association between peripheral arterial disease and depressive symptoms have yielded conflicting results. In a sample of 167 men and women clinic patients, using similar assessment instruments, Arseven et al [9] was unable to find an association between depressive symptoms and ABI. In another study consisting of a larger population with 4019 men and women aged 60 years or older, Tiemier et al [11] investigated the association between depression and atherosclerosis.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation